Stereo Vision Using Compensation Technique For Improvement Of Distance Measurement Accuracy For Robot Arm Applications - Eng, Swee Kheng (2012)
Two-Dimensional (2D) vision systems have been widely applied to various automation fields in order to increase productivity. However, these 2D vision systems are not able to retrieve the third dimension (depth) of the object. Therefore, the most promising solution to this problem is to apply the Three-Dimensional (3D) vision system to the automation fields. Among the 3D vision range finding method, stereo vision is most effective way of realizing the 3D vision. This research uses a pair of cameras as a stereo vision module to locate the object. The stereo vision system, which consists of camera calibration, image rectification, image segmentation, centroid computation and object localization is implemented. Image segmentation is performed through a process of edge-based segmentation, mathematical morphology and largest area selection. The x, y coordinates are given by the centroid coordinates of the object in the left image and the z coordinates are computed based on the obtained disparity value. The grayscale left and right images are successfully aligned horizontally through the image rectification process. The disparity error is minimized after the image segmentation process. The x coordinates result for mean and standard deviation of error are -0.14 cm and 0.19cm, respectively. The mean of error for y coordinates is -0.10 cm and the standard deviation of error for y coordinates is 0.48 cm. The initial mean and standard deviation of error for z coordinates are 0.37 cm and 0.42 cm, respectively. However, after compensation technique is performed, the mean and standard deviation of error for the z coordinates are reduced to -0.12 cm and 0.16 cm, respectively. The 3-degree of freedom robot arm can pick up a ball with the 3D location provided by the stereo vision system.